Autoimmune Progressive Fibrosing Interstitial Lung Disease: Predictors of Fast Decline - Nagy, Alexandra; Nagy, Tamas; Kolonics-Farkas, Abigel Margit; Eszes, Noemi; Vincze, Krisztina; Barczi, Eniko; Tarnoki, Adam Domonkos; Tarnoki, David Laszlo; Nagy, György; Kiss, Emese; Maurovich-Horvat, Pal; Bohacs, Aniko; et al. (Frontiers in Pharmacology, 2021)
A subset of ILD-s with autoimmune traits - including connective tissue disease-associated ILD (CTD-ILD) and interstitial pneumonia with autoimmune features (IPAF) - develop progressive fibrosing (PF)-ILD. The aim of our study was to evaluate the clinical characteristics and predictors of longitudinal lung function (LF) changes in autoimmune PF-ILD patients in a real-world setting. All ILD cases with confirmed or suspected autoimmunity discussed at the multidisciplinary team (MDT) between January 2017 and June 2019 (n=511) were reviewed, including 63 CTD-ILD and 44 IPAF patients. Detailed medical history, LF, diffusing capacity of the lung for carbon monoxide (DLCO), 6 minute walk test (6MWT), blood gas analysis (BGA) and high resolution computer tomography (HRCT) was performed. Longitudinal follow-up for functional parameters was at least 2 years. Women were overrepresented (70.1%), IPAF age was significantly higher as compared to the CTD-ILD group (p<0.001). Dyspnea, crackles and weight loss were significantly more common in the IPAF group as compared to the CTD-ILD group (84.1% vs. 58.7%, p= 0.006; 72.7%, vs. 49.2%, p< 0.017; 29.6% vs. 4.8%, p= 0.001). Forced vital capacity (FVC) yearly decline was more pronounced in IPAF (53.1±0.3 vs. 16.7± 0.2 ml; p=0.294), while the majority of patients (IPAF: 68% and CTD-ILD 82%) did not deteriorate. Factors influencing progression included malignancy as a comorbidity, anti-SS-A antibodies and post-exercise pulse increase at 6MWT. Antifibrotic therapy was administered significantly more often in IPAF as compared to CTD-ILD patients (n= 13; 29.5% vs. n=5; 7.9% vs. p=0.007) and importantly this treatment reduced lung function decline when compared to non-treated patients. Majority of patients improved or were stable regarding lung function and autoimmune associated PF-ILD was more common in patients having IPAF. Functional decline predictors were anti-SS-A antibodies and marked post-exercise pulse increase at 6MWT. Antifibrotic treatments reduced progression in progressive fibrosing CTD-ILD and IPAF emphasizing the need for guidelines including optimal treatment start and combination therapies in this special patient group.